2010
DOI: 10.1128/jvi.02311-09
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Substitution in the Capsid of Foot-and-Mouth Disease Virus Can Increase Acid Lability and Confer Resistance to Acid-Dependent Uncoating Inhibition

Abstract: The acid-dependent disassembly of foot-and-mouth disease virus (FMDV) is required for viral RNA release from endosomes to initiate replication. Although the FMDV capsid disassembles at acid pH, mutants escaping inhibition by NH 4 Cl of endosomal acidification were found to constitute about 10% of the viruses recovered from BHK-21 cells infected with FMDV C-S8c1. For three of these mutants, the degree of NH 4 Cl resistance correlated with the sensitivity of the virion to acid-induced inactivation of its infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(122 citation statements)
references
References 68 publications
12
109
1
Order By: Relevance
“…The acid sensitivity of FMDV has been related to the mechanism of virus penetration in host cells (13)(14)(15); the current model supports the hypothesis that the acidification of endosomes, where FMDV virions are sorted, triggers viral uncoating and genome release (16)(17)(18). Consistently, blockage of endosome acidification using the lysosomotropic weak base ammonium chloride (NH 4 Cl), which acts as a proton sink within the endosomes (19,20), inhibited FMDV infection by impairing virus uncoating without affecting virus binding or entry (10,13,21). We previously reported that under the conditions of impaired acidification of endosomes in cells treated with NH 4 Cl, FMDV variants with enhanced acid sensitivity could be selected (10).…”
Section: The Viral Capsid Protects the Viral Genome From Environmentasupporting
confidence: 77%
See 4 more Smart Citations
“…The acid sensitivity of FMDV has been related to the mechanism of virus penetration in host cells (13)(14)(15); the current model supports the hypothesis that the acidification of endosomes, where FMDV virions are sorted, triggers viral uncoating and genome release (16)(17)(18). Consistently, blockage of endosome acidification using the lysosomotropic weak base ammonium chloride (NH 4 Cl), which acts as a proton sink within the endosomes (19,20), inhibited FMDV infection by impairing virus uncoating without affecting virus binding or entry (10,13,21). We previously reported that under the conditions of impaired acidification of endosomes in cells treated with NH 4 Cl, FMDV variants with enhanced acid sensitivity could be selected (10).…”
Section: The Viral Capsid Protects the Viral Genome From Environmentasupporting
confidence: 77%
“…In contrast, the most acid-labile viruses were those carrying amino acid replacements VP3 A116V and VP3 A118V (pH 50 s, 6.87 and 6.93 [10], respectively). The VP3 A116V ϩ VP1 N17D double mutant (pH 50 , 6.67) displayed an intermediate phenotype between acid-resistant and acid-labile viruses, with an inactivation profile similar to that of C-S8c1 virus (pH 50 , 6.65 [10,11]). Therefore, these results indicated that the introduction of replacement VP1 N17D into a highly acid-labile capsid carrying replacement VP3 A116V increased virion acid resistance to a level similar to that of the parental C-S8c1 virus, with minor effects on viral growth.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations